Gambaran Pengelolaan Bank Sampah Di Kabupaten Mamuju - Putri, Nur Amanda; Ganing, Abdul; Akbar, Fajar; Haeruddin, Miftah Chairani (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Mamuju, 2024)
Garbage is still a problem for the environment to this day, and if waste is not handled properly it will have an impact that can harm living things, especially humans. The waste bank is a waste management system that has been developed by the Mamuju district government since 2019. Currently, 6 active BSUs have been formed. BSU is only 25% and has reduced waste by 13% of the total generation. The type of research used in this research is qualitative research, using in-depth interviews. Informants in this study were taken from the Head of the Mamuju Regency Environment and Sanitation Service and the leadership of the BSI Manakarra Keren Bank and BSI waste bank customers . The results of research on the service performance of the Mamuju Regency waste bank related to productivity, service quality and responsibility found that the waste production that can be reduced over the last 2 years is 9,203.3 kg. The aspect of service quality seen from the provision of waste storage facilities and infrastructure at the waste bank has not yet increased efforts to sort waste, services carried out by the waste bank with the aspirations of the community. Of the total population of 293,326 people (2019) only 238 are customers at the Garbage Bank who participate in BSI as customers, where the success indicator for the performance of the main Garbage Bank service is also based on the number of customers and activity The unit waste bank, the research shows that the performance of BSI is still low. The suggestion from this study is that BSI needs assistance with the management of the unit waste bank providing infrastructure facilities, awareness and campaigns about the existence of a waste bank through outreach.